MODEL SIMULATION OF GEOMETRY AND STRESS-STRAIN VARIATION OF BATAN FUEL PIN PROTOTYPE DURING IRRADIATION TEST IN RSG-GAS REACTOR - Suwardi Suwardi; Winter Dewayatna; Sungkono Sungkono; Ridwan Ridwan; M Rifai (website, 2015)
MODEL SIMULATION OF GEOMETRY AND STRESS-STRAIN VARIATION OF BATAN FUEL PIN PROTOTYPE DURING IRRADIATION TEST IN RSG-GAS REACTOR*). The first short fuel pin containing natural UO2 pellet in Zry4 cladding has been prepared at the CNFT (Center for Nuclear Fuel Technology) then a ramp test will be performed. The present work is part of designing first irradiation experiments in the PRTF (Power Ramp Test Facility) of RSG-GAS 30 MW reactor. The thermal mechanic of the pin during irradiation has simulated. The geometry variation of pellet and cladding is modeled by taking into account different phenomena such as thermal expansion, densification, swelling by fission product, thermal creep and radiation growth. The cladding variation is modeled by thermal expansion, thermal and irradiation creeps. The material properties are modeled by MATPRO and standard numerical parameter of TRANSURANUS code. Results of irradiation simulation with 9 kW/m LHR indicates that pellet-clad contacts onset from 0.090 mm initial gaps after 806 d, when pellet radius expansion attain 0.015 mm while inner cladding creep-down 0.075 mm. A newer computation data show that the maximum measured LHR of n-UO2 pin in the PRTF 12.4 kW/m. The next simulation will be done with a higher LHR, up to 25 kW/m.MODEL SIMULASI VARIASI GEOMETRI DAN STRESS-STRAIN DARI PROTOTIP BAHAN BAKAR PIN BATAN SELAMA UJI IRADIASI DI REAKTOR RSG-GAS. Pusat Teknologi Bahan Bakar Nuklir (PTBBN) telah menyiapkan tangkai (pin) bahan bakar pendek perdana yang berisi pelet UO2 alam dalam kelongsong paduan zircaloy untuk dilakukan uji iradiasi daya naik. Penelitian ini merupakan bagian dari perancangan percobaan iradiasi pertama di PRTF (Power Ramp Test Fasility) yang terpasang di reaktor serbaguna RSG-GAS berdaya 30 MW. Telah dilakukan pemodelan dan simulasi kinerja termal mekanikal pin selama iradiasi. Variasi geometri pelet dan kelongsong selama pengujian dimodelkan dengan memperhatikan fenomena ekspansi termal, densifikasi, bengkak oleh produk fisi, creep termal dan pertumbuhan iradiatif. Variasi sifat kelongsong dimodelkan oleh ekspansi termal, termal dan creep iradiatif. Sifat material dimodelkan dengan MATPRO serta parameter numerik standar kode TRANSURANUS. Hasil iradiasi simulasi dengan laju daya 9 kW/m, 75% data daya aksimal, menunjukkan bahwa awal kontak fisik pelet dengan kelongsong dari celah awal 0,09 mm terjadi setelah 806 hari, ketika ekspansi jejari pelet mencapai 0,015 mm sementara jejari kelongsong menyusut 0,075 mm. Data terbaru menunjukkan bahwa perhitungan maksimal dan pengukuran laju daya linear tangkai bahan bakar berisi UO2 alam di PRTF adalah 12,4 kW/m pada daya reactor 15 kW. Penelitian selanjutnya akan dilakukan dengan LHR lebih tinggi, sampai 25 kW / m, bila daya reactor 30 MW.Keywords: iradiasi, pin bahan bakar, UO2 alam, geometri, tegangan-regangan.